Secure Cloud Medical Data Using Optimized Homomorphic Encryption - et. al., S. Gnana Sophia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Protection of medical images on the virtual transmission platform is a simple and demanding activity, using multiple techniques to protect the digital file, such as cryptography, steganography and watermarking. This are the digital image protection approaches to meet security goals, i.e. confidentiality, trustworthiness, and usability. In this paper, the medical images are deposited in the cloud utilizing optimized homomorphic encryption. To increase the security level Rider Optimization Algorithm (ROA) is utilized to select the optimal key. Homomorphic encryption is a method of authentication which helps one to perform observes of the encrypted information through decrypting it. When the data is decrypted, the calculation consequence is stable, the same as if the procedures were conducted on the unprotected data. After completing the encrypted data, the encrypted images can be stored in the cloud and the decryption the same process is utilized to reconstruct the original images. For the experimental analysis, the performance of the proposed method is analyzed by the various parameters such as execution time, encryption time, and decryption time. The execution time of the proposed method is 2% decrease the HE existing method and 4% reduce the ECC algorithm.